2021
DOI: 10.14639/0392-100x-n1033
|View full text |Cite
|
Sign up to set email alerts
|

The Video Head Impulse Test in the acute stage of posterior canal benign paroxysmal positional vertigo

Abstract: SUMMARY Objective Study the high-frequency vestibulo-oculomotor reflex in posterior canal benign paroxysmal positional vertigo (BPPV) through Video Head Impulse Test (vHIT). Methods 150 patients suffering for the first time from posterior canal BPPV were studied. Posterior canal vestibulo ocular reflex (VOR) gain was analysed through stimulations in right anterior-left posterior and left anterior-right posterior planes before treatment, immediately after re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…A partial canal jam might determine impaired responses for high-frequency stimuli, such as head impulses in v-HIT, whereas low-frequency stimuli, such as the cupular stimulus of the endolymph flow activated during the positional test, remain active (low-pass filter). Data reported by Castellucci et al 23 highlight the difference between APC and TPC, in which the posterior canal VOR gain is not affected 24 .…”
Section: Discussionmentioning
confidence: 90%
“…A partial canal jam might determine impaired responses for high-frequency stimuli, such as head impulses in v-HIT, whereas low-frequency stimuli, such as the cupular stimulus of the endolymph flow activated during the positional test, remain active (low-pass filter). Data reported by Castellucci et al 23 highlight the difference between APC and TPC, in which the posterior canal VOR gain is not affected 24 .…”
Section: Discussionmentioning
confidence: 90%
“…Several explanations have been proposed. Disturbance of endolymphatic hydrodynamics in the posterior SCC due to free-floating particles (canalithiasis) has been suggested ( 21 ), but this hypothesis remains controversial as other investigators found no significant impairment of VOR gain for the affected posterior SCC in patients with PC-BPPV involving the ampullary arm ( 22 , 23 ). Canalith jam, either partial or complete type, could lead to decreased VOR gain in response to vHIT.…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with persistent positional DBN, with or without torsion in the DH positions and SHHP and without nystagmus on return to upright, the video head impulse test (vHIT) was able to detect the involved vertical canal of the coplanar pair, either PC-BPPV canal obstruction or AC-BPPV ( 36 , 37 ). However, in typical acute PC-BPPV, the vHIT was unable to identify the involved canal ( 38 ). In this case, the vHIT was not used to identify the involved canal.…”
Section: Discussionmentioning
confidence: 99%